Produktiviti bagi sistem pengajian tinggi di Malaysia - Chan, Lee Yee; Abdullah, Norehan (Universiti Sains Malaysia Press, 2007)
This paper tries to analyse the productivity issue in Malaysia’s higher education system. Productivity is the ratio of output per input.However, it is difficult to measure the output of higher education because the quality of graduates is intangible.Most research are focused on quality measurement of higher education or using the least cost solution that emphasizes quantity rather than quality and efficiency regardless of effectiveness.The objectives of this paper are to determine the best measurement to measure the productivity in Higher Education Institution (HEI), and to identify the relationships between efficiency of higher education system and graduates’ unemployment.Using Universiti Utara Malaysia (UUM) as a case study, productivity’s measurement is divided into two categories: efficiency and effectiveness.Efficiency measures the ratio of total number of students in UUM and total cost; the effectiveness analyses how UUM fulfills the needs of society. Also, regression analyses are used to estimate the relationship between total unemployed graduates and education cost; and cost of higher education cost.This study found that the productivity of UUM is relatively low as only half of the total graduates are employed three months after leaving the university, and more than 40% of the total graduates fall into the category of unemployment.Regression analyses show a significant and positive relationship between efficiency of higher education system and graduates’ unemployment.